2017
DOI: 10.1038/cddis.2016.460
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation mediates radiation-induced pyroptosis in bone marrow-derived macrophages

Abstract: A limit to the clinical benefit of radiotherapy is not an incapacity to eliminate tumor cells but rather a limit on its capacity to do so without destroying normal tissue and inducing inflammation. Recent evidence reveals that the inflammasome is essential for mediating radiation-induced cell and tissue damage. In this study, using primary cultured bone marrow-derived macrophages (BMDM) and a mouse radiation model, we explored the role of NLRP3 inflammasome activation and the secondary pyroptosis underlying ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 45 publications
3
99
0
Order By: Relevance
“…Our evaluation found that NLRP3, one of the most widely researched members of inflammasome complexes, was the gene relevant to this process. Interestingly, Liu et al concluded the Nlrp3 inflammasome activation mediates radiation‐induced pyroptosis in primary cultured bone marrow‐derived macrophages, suggestion that targeting NLRP3 inflammasomes may serve as a potential strategy to mitigate RT‐induced damage . Of note, the addition of ALA administration to RT diminished XRT‐induced Nlrp3 inflammasome activation and the resultant secretion of IL‐1b in rectal tissues (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Our evaluation found that NLRP3, one of the most widely researched members of inflammasome complexes, was the gene relevant to this process. Interestingly, Liu et al concluded the Nlrp3 inflammasome activation mediates radiation‐induced pyroptosis in primary cultured bone marrow‐derived macrophages, suggestion that targeting NLRP3 inflammasomes may serve as a potential strategy to mitigate RT‐induced damage . Of note, the addition of ALA administration to RT diminished XRT‐induced Nlrp3 inflammasome activation and the resultant secretion of IL‐1b in rectal tissues (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…hypo versus hyper fxMouse colonBarlow et al (2016) IL-1α, IL-1β, TNF-αX-ray versus γ-ray ( 137 Cs)7–25 Gy/1fxMouse brainHong et al (1995) IL-β, TNF-αγ-ray ( 137 Cs)10 Gy/1fxRat brainLee et al (2010) IL-6γ-ray ( 60 Co)10 Gy/1fxHuman alveolar carcinoma cells (A549)Gao et al (2014) IL-1β, TNF-αα-particle ( 3 He) microbeam0.5 Gy/1fxHuman lung fibroblastsZhou et al (2008) IL-6γ-ray ( 60 Co or 137 Cs)9–10 Gy/1fxMouse plasma and lungVan der Meeren et al (2003) TNF-αγ-ray ( 192 Ir)10 Gy/1fxRat brain(Kim et al 2002) IL-1α, TNF-αγ-ray ( 137 Cs)0–35 Gy/1fxMouse brainMoravan et al (2011) TNF-αX-ray2–20 Gy/1fx versus 10–40 Gy/5–20fxMouse brainGaber et al(2003) IL-1α, IL-6X-ray12 Gy/1fxMouse lung, bronchial lavage fluid, serumAo et al (2009) IL-8α-particle ( 238 Pu)0.036–0.19 Gy/1fxHuman lung fibroblastsNarayanan et al (1999) IL-1α, IL-1β, IL12p40, IL-18, TNF-α, IFN-γγ-ray ( 60 Co)5–20 Gy/1fxMurine bone marrow-derived macrophagesLiu et al (2017)Anti-inflammatory cytokines TGF-β1γ-ray ( 192 Ir)…”
Section: Radiation-induced Immune Mediatorsmentioning
confidence: 99%
“…b-g show the MRS of the different groups. The NAA/Cr ratio in the 15 Gy group and 25 Gy group was significantly lower than that in the control group on the 4th day after radiation injury, but the ratios at 8 weeks were partially recovered 3 h after irradiation in a dose-dependent manner [31]. These authors also showed that 10 Gy radiation in vivo induced pyroptosis and caspase-1 activation.…”
Section: Discussionmentioning
confidence: 83%